Utilization and Evaluation of Analgesics in Post Gynecologic Operations: A Cross- Sectional Study - Mohammad-Reza Alizadeh; Sana Hamedani; Hadi Saghaleini; Elnaz Shaseb (Research Center for Rational Use of Drugs (RCRUD), 2023)
Background: This study evaluated the current practices of opioid and non-opioid analgesic administration for postoperative pain management in gynecological surgeries, aiming to optimize pain relief while minimizing side effects. Methods: A cross-sectional, prospective Drug Utilization Evaluation (DUE) study was conducted at Al-Zahra Hospital, Tabriz, Iran. Medical records of 100 patients undergoing gynecological surgery were reviewed over five months. Data on prescribed analgesics, pain scores, and adherence to APS2016 and ERAS2016 guidelines were collected and analyzed statistically. Results: Meperidine (pethidine) and diclofenac were the most frequently prescribed analgesics. The average patient pain score was 2.48 units. A combination of meperidine, diclofenac, and acetaminophen was identified as the most effective regimen for pain control. Prescribed regimens demonstrated 41.4±27.3% theoretical and 60.60 ± 28.77% practical compliance with APS2016 and ERAS2016 guidelines. While achieving the primary objective of pain relief with minimal side effects, compliance with established guidelines could be further improved through educational interventions. Conclusion: Optimizing analgesic regimens for postoperative pain management requires careful consideration of individual patient needs, including the benefits of opioid analgesics in achieving greater pain reduction. Adherence to evidence-based guidelines and ongoing educational programs for healthcare professionals are crucial for ensuring optimal pain relief with minimal side effects.